1996
DOI: 10.1076/apab.104.1.30.12864
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Smooth Muscle Reactivity and Endothelium Derived Relaxing Factor in Experimental Obstructive Jaundice

Abstract: Obstructive jaundice is associated with a predisposition to systemic hypotension and acute renal failure. Altered vascular reactivity may contribute to the development of hypotension. In this experimental study on dogs, alterations in vascular contractile responses to noradrenaline, serotonin and KCl were investigated. Contractile responses to noradrenaline, serotonin,,, KCL and relaxation responses to papaverin and acetylcholine were provoked in isolated femoral arteries of both control dogs and animals with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Many investigators have concentrated on a possible alteration in vascular tone as an explanation for these clinical findings. An increased incidence of acute renal failure in patients with obstructive jaundice and alterations in vascular reactivity to various agents have been suggested, 5,7,12,17–19 but the data concerning the sensitivity of peripheral vasculature to vasoactive amines have been conflicting. 3–8 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many investigators have concentrated on a possible alteration in vascular tone as an explanation for these clinical findings. An increased incidence of acute renal failure in patients with obstructive jaundice and alterations in vascular reactivity to various agents have been suggested, 5,7,12,17–19 but the data concerning the sensitivity of peripheral vasculature to vasoactive amines have been conflicting. 3–8 …”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the endothelium‐dependent response to ACh was higher in BDL dogs than in control dogs, thus confirming our previous report. 12 Furthermore, the magnitude of the precontraction was similar in preparations from SO and BDL dogs for PE, thus ensuring that any difference in relaxation between any SO and BDL preparations was not due to differences in the degree of precontraction. In the present study, the relaxation responses to papaverine were similar between the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incremental doses of BAs induced vasorelaxation irrespective of blocking agents or denudement of the endothelium showing that the action is probably mediated through inhibition of calcium entry through membranary channels. This is highly influenced by the type of bile acid and indeed it seems that hydrophobic and lypophilic BAs are more likely to induce vasorelaxation . The authors speculated on the mechanism by which bile acids accomplish this effect and concluded that it must be through direct interaction with components of the cellular membrane.…”
Section: Bile Acids and Cardiovascular Functionmentioning
confidence: 99%
“…This is highly influenced by the type of bile acid and indeed it seems that hydrophobic and lypophilic BAs are more likely to induce vasorelaxation. 73 The authors speculated on the mechanism by which bile acids accomplish this effect and concluded that it must be through direct interaction with components of the cellular membrane.…”
Section: Incremental Doses Of Bas Induced Vasorelaxation Irrespectivementioning
confidence: 99%